Increased hippocampal epigenetic age in the Ts65Dn mouse model of Down Syndrome - Ravaioli, Francesco; Stagni, Fiorenza; Guidi, Sandra; Pirazzini, Chiara; Garagnani, Paolo; Silvani, Alessandro; Zoccoli, Giovanna; Bartesaghi, Renata; Bacalini, Maria Giulia (Frontiers in Aging Neuroscience, 2024)
Down syndrome (DS) is a segmental progeroid genetic disorder associated to multi-systemic precocious aging phenotypes, which are particularly evident at the immune and nervous systems. Accordingly, people with DS show an increased biological age as measured by epigenetic clocks. The Ts65Dn trisomic mouse, which harbors extra-numerary copies of chromosome 21 (Hsa21)-syntenic regions, was shown to recapitulate several progeroid features of DS, but no biomarkers of age have been applied to it so far. In this pilot study, we used a mouse specific epigenetic clock to measure epigenetic age of hippocampi from Ts65Dn and euploid mice at 20 weeks. Ts65Dn mice showed an increased epigenetic age in comparison with controls, and the observed changes in DNA methylation partially recapitulated those observed in hippocampi from people with DS. Collectively, our results support the use of the Ts65Dn model to decipher the molecular mechanisms underlying the progeroid DS phenotypes.